PSYCHOLOGICAL NEEDS OF DEMENTIA PATIENTS IN SOCIAL CARE INSTITUTION: A QUALITATIVE STUDY - Terehova, Rudite (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Psychological needs are present in all human beings, but are likely to be heightened for people with dementia because they are usually more vulnerable and less likely to be able to take action to satisfy these needs. The open, unstructured interviews of six patients with dementia were performed with the aim of clarifying their psychological needs in the social care institution. Key themes, derived from interviews: the need for emotional support; the need to maintain autonomy and independence; the need for dignified attitude; the need to participate in decision making and control their lives; the need to preserve the sense of identity; the need to engage in meaningful activities. One expert - social rehabilitator – was interviewed to find out, in which areas dementia patients need psychological support. The expert interview discovered the following themes: dignified attitude; emotional support; meaningful activities; the sense of identity. Increased competence of understanding psychological needs and how those needs can be met, are essential for delivering high-quality care for persons with dementia living in social care institutions.